Pembelajaran Pembuatan Pakan Mandiri dan Penstimulan Moulting Udang bagi Pembudidaya Tradisional: The Learning to Make Independent Feed and Shrimp Moulting Stimulant for Traditional Farmers - Heriansah, Heriansah; Nursyahran, Nursyahran; Fathuddin, Fathuddin; Kabangnga, Arnold; Najamuddin, Najamuddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Shrimp farming in Indonesia is dominated by traditional cultivation methods, therefore they do not have sufficient financial access to obtain expensive commercial feed. The Program for Application of Appropriate Technology (PTTG) aims to provide lessons on making independent feed and stimulating shrimp moulting for traditional farmers in Ma'rang District, Pangkajene and Islands Districts using local raw materials. The Participatory Rural Appraisal (PRA) approach model, which emphasizes the active involvement of the community in all activities, is used in this program. The knowledge and skills transferred from this study include the concept of artificial feed and moulting, preparation of raw materials, preparation of feed composition, mixing and weighing of raw materials, and pelleting and supplementation of feed. The results of the pre-test showed that the level of knowledge and skills regarding self-sufficient feed production and the manufacture of moulting-stimulating ingredients were generally in the poor category. However, after the learning activities, the post-test results showed that the level of knowledge and skills increased significantly and was generally in the good category. In general, partners believe that learning items are technically easy to apply, economically inexpensive, and ecologically can reduce agricultural and fishery waste. The lessons learned by traditional cultivators through this program can be utilized optimally in increasing production.